Impact of income diversification on rural livelihood in some selected areas of Bangladesh: Diversification strategies and rural welfare (Journal of the Bangladesh Agricultural University, 2019)
Diverse set of income generating activities may have varying effect on household’s welfare situation. This study intends to assess the extent of different income diversification strategies on rural household welfare. A total sample of 153 households from three districts of Bangladesh was randomly selected. Considering simultaneous causality between different livelihood strategies and welfare indicators, the Two Stage Least Square (2SLS) methods with instrumental variable was applied to estimate impact of the strategies on household welfare. Household per capita expenditure was treated as the welfare indicator which includes both food and non-food expenditures. The findings show that involving in any type of non-farm activities jointly with farming has a significantly positive effect on the household’s welfare. Among different non-farm activities, participation in wage employment and migration along with agricultural activities ensured significantly higher per capita household expenditure. On the other hand, the impact of currently participation in only agricultural activities on household expenditure is insignificant. Besides, Farm size, higher education and infrastructural facilities also play an important role in improving household’s welfare. Therefore, policy should be directed to create opportunities to participate in non-farm activities through establishment of small and medium industries, especially agro-based industries in the rural areas.J. Bangladesh Agril. Univ. 17(1): 73–79, March 2019